Conformational basis for the biological activity of TOAC-labeled angiotensin II and bradykinin: Electron paramagnetic resonance, circular dichroism, and fluorescence studies - Schreier, Shirley; Barbosa, Simone R.; Casallanovo, Fábio; Vieira, Renata de F. F.; Cilli, Eduardo Maffud [UNESP]; Paiva, Antonio C. M.; Nakaie, Clóvis R. [UNESP] (Wiley, 2004)
N-Terminally and internally labeled analogues of the hormones angiotensin (AII, DRVYIHPF) and bradykinin (BK, RPPGFSPFR) were synthesized containing the paramagnetic amino acid 2,2,6,6-tetramethylpiperidine-1-oxyl-4-amino-4- carboxylic acid (TOAC). TOAC replaced Asp 1 (TOAC 1-AII) and Val 3 (TOAC 3-AII) in AII and was inserted prior to Arg 1 (TOAC 0-BK) and replacing Pro 3 (TOAC 3-BK) in BK. The peptide conformational properties were examined as a function of trifluoroethanol (TFE) content and pH. Electron paramagnetic resonance spectra were sensitive to both variables and showed that internally labeled analogues yielded rotational correlation times (TC) considerably larger than N-terminally labeled ones, evincing the greater freedom of motion of the N-terminus. In TFE, τ C increased due to viscosity effects. Calculation of τ Cpeptide/τ CTOAC ratios indicated that the peptides acquired more folded conformations. Circular dichroism spectra showed that, except for TOAC 1-AII in TFE, the N-terminally labeled analogues displayed a conformational behavior similar to that of the parent peptides. In contrast, under all conditions, the TOAC 3 derivatives acquired more restricted conformations. Fluorescence spectra of All and its derivatives were especially sensitive to the ionization of Tyr 4. Fluorescence quenching by the nitroxide moiety was much more pronounced for TOAC 3-AII The conformational behavior of the TOAC derivatives bears excellent correlation with their biological activity, since, while the N-terminally labeled peptides were partially active, their internally labeled counterparts were inactive [Nakaie, C. R., et al., Peptides 2002, 23, 65-70]. The data demonstrate that insertion of TOAC in the middle of the peptide chain induces conformational restrictions that lead to loss of backbone flexibility, not allowing the peptides to acquire their receptor-bound conformation. © 2004 Wiley Periodicals, Inc.
Keywords: Angiotensin II; Bradykinin; Circular dichroism; EPR; TOAC; Carboxylic acids; Fluorescence; Ionization; Paramagnetic resonance; pH; Polypeptides; Quenching; Viscosity; Angiotensin; Correlation times; Viscosity effects; Biopolymers; 2,2,6,6, tetramethylpiperidine 1 oxyl 4 amino 4 carboxylic acid; angiotensin; bradykinin; carboxylic acid derivative; nitroxide; trifluoroethanol; unclassified drug; amino terminal sequence; circular dichroism; conformational transition; derivatization; drug activity; electron spin resonance; fluorescence; phase transition; photochemical quenching; protein conformation; protein folding; receptor binding; spin labeling; viscosity; Animals; Circular Dichroism; Cyclic N-Oxides; Electron Spin Resonance Spectroscopy; Hydrogen-Ion Concentration; Protein Conformation; Spectrometry, Fluorescence; Spin Labels; Structure-Activity Relationship; insertion sequences